"Should've known better": Counterfactual processing in disordered gambling. (January 2021) - Wu, Yin; Kennedy, Dawn; Goshko, Caylee-Britt; Clark, Luke
Highlights: Regret and counterfactual thinking are relevant to decision biases in gambling. We compared groups with gambling disorder and healthy controls on a choice task. The group with gambling disorder showed higher regret anticipation. Affect ratings were blunted in gambling disorder to obtained and counterfactual feedback. Abstract: Counterfactual thinking is a component of human decision-making that entails "if only" thinking about unselected choices and outcomes. It is associated with strong emotional responses of regret (when the obtained outcome is inferior to the counterfactual) and relief (vice versa). Counterfactual thinking may play a role in various cognitive phenomena in disordered gambling, such as the effects of near-misses. This study compared individuals with gambling disorder (n = 46) and healthy controls (n = 25) on a behavioural economic choice task that entailed choosing between two gambles, designed to measure counterfactual thinking. Participants provided affect ratings following both the obtained and the non-obtained outcomes. Choices were analyzed using a computational model that derived parameters reflecting sensitivity to expected value, risk variance, and anticipated regret. In the computational choice model, the group with gambling disorder showed increased sensitivity to anticipated regret, reduced sensitivity to expected value, and increased preference for high risk-variance gambles. On the affect ratings, the group with gambling disorder displayed blunted emotional sensitivity to obtained and counterfactual outcomes. Effect sizes of the group differences were modest. Participants with gambling disorder show wide-ranging alterations in decision-making processes and emotional reactivity to choice outcomes. Altered sensitivity to anticipatory regret in gambling disorder may contribute to the development of gambling-related cognitive distortions, and the influences of gambling marketing.